Pengaruh Variabel Kualitas Air terhadap Produktivitas Udang Vaname (Litopenaeus vannamei) di Kawasan Pertambakan Kabupaten Gresik, Jawa imur - A. Marsambuana Pirzan; Utojo Utojo (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
Water quality variable to affect the productivity of Pacific white shrimp (L. vannamei) in the brackishwater ponds. Therefore the aimed of this research to study the water quality variable to influent on the productivity of Pacific white shrimp (L. vannamei) in the brackishwater ponds. The research was conducted in the brackishwater ponds area that were in fish farming operation in the brackishwater ponds in the brackishwater ponds of Gresik Regency, East Java Province by conducting interviews with respondents to obtained primary data in the brackishwater ponds productivity through the submission of questionnaires, while the technical data of water quality variable were obtained by direct measurement in situ. As independent variable were water quality variables, namely: temperature, dissolved oxygen (DO), salinity, pH, total suspended solid (TSS), turbidity, nitrate, nitrite, phosphate, and total organic matter (TOM) while the dependent variable was the productivity of Pacific white shrimp. Regression model selection “best” method was based on the backward. The results showed that productivity of Pacific white shrimp in the range from 133.3 to 3,000 kg / ha with an average of 690.38 kg / ha. Water quality variables that a have positive effect on the productivity of Pacific white shrimp were nitrate and phosphate, while water quality variables have a negative effect on the productivity of Pacific white shrimp. were pH and TSS.